Can Peripartum Plasma Profiles of Steroid Hormones, Metabolites and Minerals Predict Postpartum Fertility in Buffaloes? - Kalasariya, R.M.; Dhami , A.J.; Parmar , S.C. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The plasma profile of various hormonal, biochemical and mineral constituents was studied in 32 buffaloes under nutritional management of transition period for 2 months before to 2 months postpartum. The buffaloes that expressed estrus and conceived within 120 days postpartum, irrespective of nutrient treatment or control groups, were classified as fertile (n=15) and rests as infertile (n=17) buffaloes. The variations in blood glucose and plasma profile of progesterone, estradiol, protein, cholesterol, triglycerides, Ca, P, Mg and trace minerals (Zn, Fe, Cu, Co, Mn), if any, on day 60, 30, 15 prepartum, on the day of calving, and on day 15, 30, 45 and 60 postpartum in postpartum conceiving and non-conceiving buffaloes were examined. There was no significant effect of fertile-infertile groups on plasma P4 and E2 profile on any day, except on day 45 postpartum, where E2 was (p<0.05) higher in fertile than infertile group (31.47±2.37 vs. 24.29±1.76 pg/ml), indicating early onset of follicular activity with ovulatory estrus in postpartum fertile group. The blood glucose and plasma protein profile also did not vary significantly at any of the intervals between two groups. Further, no significant difference in plasma cholesterol or triglyceride concentrations was found between conceived and non-conceived buffaloes at any of the intervals pre- or postpartum, except that the pooled mean cholesterol level was higher (P<0.05) in non-conceived than conceived buffaloes. The plasma concentrations of calcium, inorganic phosphorus and magnesium also did not reveal significant variation between fertile and infertile buffaloes at any of the intervals, though the magnesium value was higher in conceived than non-conceived buffaloes. Similarly, no significant difference was seen in the levels of plasma trace minerals, viz., Zn, Fe, Mn, Cu or Co between fertile and infertile buffaloes at any of the intervals studied. These non significant variations noted between fertile and infertile buffaloes in blood profile could perhaps be due to masking effect of nutritional supplementation as the control group was also optimally managed by the farmers; hence the animals were pooled irrespective of groups for this comparison.